ANALYSIS OF DETERMINANTS OF THE ENVIRONMENTAL QUALITY INDEX IN SIX PROVINCES OF JAVA ISLAND - Millatul Khoiriyah; Anik Sri Widawati (Universitas Gunadarma, 2026)
Environmental quality is an important indicator that reflects the sustainability of ecosystems and the welfare of communities in a region. The Environmental Quality Index (EQI) provides a quantitative measure of environmental quality in an area over a given period, derived from the Water Quality Index (WQI), Air Quality Index (AQI), Land Quality Index (LQI), and Marine Water Quality Index (MWQI). To date, Java Island has consistently had the lowest LQI among Indonesian islands. This study was conducted to determine the effect of access to proper drinking water, access to adequate sanitation, population density, land transportation, and the number of large and medium industries on the Environmental Quality Index (EQI) in 6 provinces on the island of Java from 2016 to 2024 using panel data regression analysis with the Fixed Effect Model (FEM) approach and Granger causality testing with 54 observations. The study found that access to safe drinking water, access to proper sanitation, population density, and the number of industries significantly affected the EQI. Land transportation did not have a significant effect on the EQI. Based on the Granger causality test, there was a reciprocal relationship between several independent variables and the EQI.